Sustainable Development Goals and Human Rights. (Springer, 2020)
This open access book analyses the interplay of sustainable development and human rights from different perspectives including fight against poverty, health, gender equality, working conditions, climate change and the role of private actors. Each aspect is addressed from a more human rights-focused angle and a development-policy angle. This allows comparisons between the different approaches but also seeks to close gaps which would remain if only one perspective would be at the center of the discussions. Specifically, the book shows the strong connections between human rights and the objectives of the 2030 Agenda for Sustainable Development and the Sustainable Development Goals adopted by the United Nations in 2015. Already the preamble of this document explicitly states that "the 17 Sustainable Development Goals ... seek to realise the human rights of all". Moreover, several goals and targets of the 2030 Agenda correspond to already existing individual human rights obligations. The contributions of this volume therefore also address how the implementation of human rights and SDGs can reinforce each other, but also point to critical shortcomings of the different approaches.
Keywords: Human rights.; Economic development -- Environmental aspects.; Sustainable development.; Economic policy.; Social justice.; Climatic changes.; Human Rights; Social Justice; Climate Change; Droits de l'homme (Droit international); Développement économique -- Aspect de l'environnement.; Développement durable.; Politique économique.; Justice sociale.; Climat -- Changements.; sustainable development.; climate change.; Development studies.; Politics & government.; Climate change.; Sustainability.; Climatic changes; Economic development -- Environmental aspects; Economic policy; Human rights; Social justice; Sustainable development; Law; Economic development--Environmental aspects; Climate change